Using words to network images: indexing and interaction strategies in a digital archive. Issue 2 (2nd April 2016) - Schumacher, Susanne
Abstract : Visual access to the content in digital archives extends the classical text search and list view of graphical user interfaces. Currently, there are several strategies employed to correlate images in the user interface of digital archives for semantic purposes. Some of the most useful strategies explore innovative techniques used to gain and execute metadata in a suitable manner. These approaches are elaborated on primarily in the context of scientific questions. Amidst these models, this article proposes a very simple strategy of networking images using only words. At present, this concept is realised at Zurich University of the Arts (ZHdK) through utilisation of the 'Media Archive of the Arts', an in-house, open source software product. It responds to user heterogeneity, the variety of intellectual genres and the multiplicity of media formats that are distinctive of an art academy such as ZHdK.